Dissecting intramural hematoma of esophagus after thrombolytic therapy: A case report. (February 2015) - Hajsadeghi, Shokufeh; Agah, Shahram; Iranpour, Aida; Chehrehgosha, Haleh; Ghanooni, Amir Hossein; Forghani, Foroogh
Esophageal hematoma is a relatively rare event. We report a case of severe chest pain associated with myocardial infarction and recurrent chest pain after administration of a thrombolytic agent. The chest pain was different from the presenting symptom and accompanied by 2 episodes of hematemesis. Esophageal hematoma was confirmed after endoscopy and computed tomography. Esophageal hematoma is a relatively rare event after thrombolytic therapy.